Detectability of the peripheral and axial manifestations of psoriatic arthritis in patients with psoriasis in dermatological practice - M. N. Chamurlieva; E. Yu. Loginova; T. V. Korotaeva (Современная ревматология, 2019)
Psoriatic arthritis (PsA) is a heterogeneous disease manifested by peripheral arthritis, dactylitis, spondylitis, and enthesitis. PsA is often undiagnosed by dermatovenerologists because of the difficulty in identifying a variety of clinical signs. The early diagnosis of PsA and the accurate assessment of all its symptoms are necessary for the timely choice of optimal therapy.Objective: to assess the detectability of clinical signs of PsA in patients with psoriasis in dermatological practice.Patients and methods. The investigation enrolled 103 patients (47 men and 56 women) (mean age, 44.0±13.7 years) with psoriasis (its mean duration, 10.7±10.2 years), the average prevalence and severity according to the Body Surface Area (BSA) and the Psoriasis Area and Severity Index (PASI) were 9.3±13.6% and 15.4±12.5 scores, respectively. All the patients completed the Psoriasis Epidemiology Screening Tool (mPEST) and were examined by a dermatovenerologist and a rheumatologist. The diagnosis of PsA was based on the Classification Criteria for Psoriatic Arthritis (CASPAR). The investigators evaluated arthritis, dactylitis, enthesitis, and inflammatory back pain (IBP) according to the rheumatological standards: IBP by the Assessment of SpondyloArthritis International Society (ASAS) criteria, and enthesitis by the Leeds Enthesitis Index (LEI).Results and discussion. Sixty-one (59.2%) of the 103 patients with psoriasis were found to have PsA on the basis of the CASPAR criteria and the rheumatologist's examination. The dermatovenerologist diagnosed arthritis in a significantly smaller number of cases than did the rheumatologist: in 15 (24.6%) and 35 (57.4%) of the 61 patients (p<0.001), respectively. The dermatovenerologist and the rheumatologist demonstrated no significant differences in their clinical evaluation of dactylitis: it was detected in 37 (60.7%) and 40 (65.6%) of the 61 patients, respectively (p=0.32). Based on patient complaints and mPEST findings, the dermatovenerologist recorded pain in the calcaneal region in 32 (52.5%) patients. The rheumatologist identified ulnar, knee, and calcaneus enthesitis in 11 (18%), 8 (13.1%), and 25 (41%) patients, respectively. Based on complaints and mPEST findings, the dermatovenerologist detected back pain in 30 (49.2%) of the 61 patients. The rheumatologist diagnosed IBP in 21 (70%) of these 30 patients and mechanical back pain in 9 (30%). Thus, IBP was noted in 34.4% of PsA patients. Tendonitis was undiagnosed by the dermatovenerologist; the rheumatologist identified wrist tendonitis in 13 (21.3%) of the 61 patients with PsA.Conclusion. Dermatovenerologists frequently underestimate damage to the spine and entheses in patients with psoriasis. The introduction of the ASAS criteria for IBP and methods for assessing enthesitis in dermatological practice can improve the early diagnosis of axial lesion in PsA in patients with psoriasis.